Estudo de conjuntos minimais para sistemas descontínuos em dimensões 2 e 3 - Euzébio, Rodrigo Donizete [UNESP] (2014)
In this thesis minimal sets of smooth and non-smooth vector fields in dimension 2 and 3 are studied. First the study of minimal sets is restricted to limit cycles. Questions about existence, distribution and quantity of such objects in smooth and non-smooth vector fields in dimension 3 are answered. Later, the existence of non-trivial minimal sets and chaos in dimension 2 is treated for non-smooth vector fields. Some examples of non-trivial minimal sets are presented and the presence of non-deterministic chaos on some of these sets is verified. Finally, a version of the Poincaré-Bendixson Theorem for non-smooth vector fields presenting neither escaping nor sliding motion is presented